Effect of Foliar Application of Potassium Fertilizer on Yield, Fruit Quality, and Cold Hardiness of Vitis spp. ‘Chambourcin’ - Gurkirat Singh; Andrea R. Gschwend; Imed E. Dami (International Journal of Fruit Science)
Temperate regions experiencing sub-zero temperatures negatively impact grapevine yield. Potassium has been claimed as a cryoprotectant to improve cold hardiness in grapevine. This study investigated the effect of foliar application of liquid potassium-based fertilizer, ReaXTM, on cold-hardiness of grapevine Vitis spp. “Chambourcin” along with its effect on yield and fruit quality. The vines were sprayed four to five times between the fruit set and veraison stage at a concentration of 1.5% (v/v) for two consecutive seasons. Petioles were analyzed for nutrients, clusters for yield and fruit quality, and cold hardiness was determined by differential thermal analysis and bud injury assessment. Potassium deficiency was observed in all treatments, and its content did not increase significantly in treated vines. Berry potassium levels and total soluble solids were generally higher in K-treated vines, however, there was no significant effect on yield and other fruit quality traits. Significant differences in cold hardiness levels were observed in both dormant seasons. Foliar application of potassium is a promising cultural practice to increase cold hardiness, but further studies are needed to understand the limits of its effectiveness.